Implementasi Pendidikan Multikultural Melalui Tongkonan Simbol Pemersatu Masyarakat Toraja - Dinarti Tandira’pak (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
Tongkonan is a traditional house of the Toraja people who coincide in the province of South Sulawesi, Indonesia. The architecture of the tongkonan house is known for its distinctive shape through the lower, middle and upper structures which have their own uniqueness or beauty. The tongkonan traditional house, which is full of carvings, has a meaning that symbolizes the social status of the owner. The tongkonan is a place for fostering a family in the unity of harmony and inheritance in every family who is descended from the tongkonan so that it becomes the forerunner which will in turn shape the personality and culture and traditions that have been passed down from generation to generation in every family group or Toraja society. Then the tongkonan which is a traditional house typical of the Toraja people which is used as a place to live, the traditional house of power to become a place of socio-cultural life for the people of Toraja. The method used in this article is the qualitative method and the data collection method is carried out, namely through direct observation which is carried out when holding ceremonies or customs carried out in society, especially the Toraja people. Based on the results of the study, it is shown that one of the implementations of multicultural education is through the tongkonan which is a symbol of unifying the Toraja people where the tongkonan is used as a place to foster kinship regardless of the differences that exist in Toraja society.